2017
DOI: 10.1007/s10897-017-0066-y
|View full text |Cite
|
Sign up to set email alerts
|

Lynch Syndrome Limbo: Patient Understanding of Variants of Uncertain Significance

Abstract: Providers and patients encounter challenges related to the management of Variants of Unknown Significance (VUS). A VUS introduces new counseling dilemmas for the understanding and psychosocial impact of uncertain genetic test results. This descriptive study uses Mishel's theory of uncertainty in illness to explore the experience of individuals who have received a VUS as part of the genetic testing process. Semi-structured interviews were conducted with 27 adult individuals who received a VUS for Lynch syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
141
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(151 citation statements)
references
References 45 publications
9
141
0
1
Order By: Relevance
“…They may have been unwilling to let go of their VUS classification as an emotional and clinical crutch, leading to a subconscious but intentional misunderstanding of their results. These findings overlap with findings from Skinner et al () and Solomon et al (). Skinner et al () described one participant that interpreted her VUS from exome sequencing as a definitive molecular diagnosis for her family history despite receiving clinical counseling on the uncertainty of the diagnosis, while Solomon et al () identified aggressive screening as a coping mechanism for uncertainty in patients who received a VUS for Lynch syndrome genes.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…They may have been unwilling to let go of their VUS classification as an emotional and clinical crutch, leading to a subconscious but intentional misunderstanding of their results. These findings overlap with findings from Skinner et al () and Solomon et al (). Skinner et al () described one participant that interpreted her VUS from exome sequencing as a definitive molecular diagnosis for her family history despite receiving clinical counseling on the uncertainty of the diagnosis, while Solomon et al () identified aggressive screening as a coping mechanism for uncertainty in patients who received a VUS for Lynch syndrome genes.…”
Section: Discussionsupporting
confidence: 86%
“…They may have been unwilling to let go of their VUS classification as an emotional and clinical crutch, leading to a subconscious but intentional misunderstanding of their results. These findings overlap with findings from Skinner et al (2017) and Solomon et al (2017). Skinner et al (2017)…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, unintentionally giving the impression that re‐contact, in the event of VUS reclassification, is contingent on research participation is problematic as research participation should not be coerced. Although not reported by our study participants, it is possible that participation in VUS reclassification studies would also aid uncertainty management for patients as has been suggested previously (Solomon et al, ). Providers could assist patients with other methods of uncertainty management—such as learning strategies to cope with uncertainty.…”
Section: Discussionmentioning
confidence: 57%
“…Genetic test results that include identification of a VUS routinely, and understandably, incite uncertainty among patients who receive this result. Patients report feelings of worry and anxiety (Makhnoon, Garrett, Burke, Bowen, & Shirts, ; Makhnoon, Shirts, Bowen, & Fullerton, ; Solomon et al, ) and higher levels of distress about cancer risk (Richter et al, ; Vos et al, ) upon receiving a VUS result. These variants are also often misinterpreted by patients as diagnostic for disease or genetic predisposition (Vos et al, ), which leads patients and providers to engage in inappropriate clinical measures (e.g., prophylactic surgery) (Murray, Cerrato, Bennett, & Jarvik, ).…”
Section: Introductionmentioning
confidence: 99%